A general method to construct single-atom catalysts supported on N-doped graphene for energy applications. Issue 13 (18th March 2020) - Liu, Linghui; Liu, Song; Li, Lu; Qi, Haifeng; Yang, Hongbin; Huang, Yanqiang; Wei, Zidong; Li, Li; Xu, Jinming; Liu, Bin
Abstract : Single atom catalysts (SACs) with atomically dispersed catalytic sites have shown great promise for energy related chemical reactions. Abstract : Single atom catalysts (SACs) with atomically dispersed catalytic sites have shown great promise for energy related chemical reactions. In this work, a facile and general approach to synthesize a large variety of transition metal (Fe, Ni, Co, Cu, etc. ) SACs with a large surface area and a hierarchical structure using layered montmorillonite (MMT) as the structural template was developed. Specifically, the as-synthesized nickel SAC (Ni-SAC) exhibits outstanding performance toward electrochemical CO2 reduction, achieving CO2 -to-CO conversion with more than 90% faradaic efficiency in the potential range from −0.6 to −1.1 V vs. RHE, and the iron SAC (Fe-SAC) displays excellent ORR activity, with the half-wave potential surpassing that of the state-of-the-art Pt/C catalyst.